Collectivity in Albers: Experimentations in Residence (Revista Apotheke, 2025)
This text presents the context of the Artistic-Pedagogical Residency of the artist and professor Carla Beatriz Franco Ruschmann, which took place at the State University of Santa Catarina (UDESC), within the project conceived by the Apotheke Painting Studio Extension Program. In the second semester of 2025, the professor attended the Pictorial Processes classes (DAV/CEART/UDESC) and participated in the Study Group on Pictorial Process, where she proposed the creation of a collective painting, composed of 25 canvases, developed from an exercise by Josef Albers (2009), the theoretical basis of the meetings held. Beyond this reference, the production was also anchored in the artistic work of the guest professor, which deals with geometric art and explores other forms and organizations that painting can take. In this way, the collective project developed sought to articulate ways of thinking together about the pictorial process with what had already been studied in the group, and from there experimenting with other ways of organizing and experiencing painting.
Keywords: Josef Albers; artistic-pedagogical residency; creativity; geometrical art; collectivity